The journalist : a Holocaust story - Lapchuk, Oxana Koval (Sunbury Press, Inc, 2019)
"The Journalist, a story unlike any other Holocaust memoir, not only depicts life in a concentration camp, but also the death marches, a bold escape, the days of wandering in the forest dodging Nazi troops, the unceasing pangs of hunger that were finally satiated, the years of searching and longing to live in a free country. This is a book you cannot put down because it draws you into the life of the journalist and compels you to keep reading to find out the outcome of his fate. Will he live to fulfill his destiny or will his life be cut short because the chances of his surviving seemed impossible? The Journalist is not just a book about how one man survived the Holocaust, but also the principles he practiced that eventually allowed him to triumph in the midst of overwhelming odds. This fast-paced true story leaves the reader breathless and astonished at the tenacity and resolve of the journalist to forge ahead when others gave up the struggle. There are many people out there who are facing challenging situations, and they need to have hope to believe that as they practice the same principles that the journalist practiced, they, too, will be able to triumph, for truly the human spirit is indomitable and can overcome any obstacle. The end result: hope that eventually produces victory over our circumstances"--